A Conservative Esthetic Approach Using Enamel Recontouring and Composite Resin Restorations. (12th October 2016) - Mathias, Paula; da Silva, Emily Vivianne Freitas; Aguiar, Thaiane Rodrigues; Andrade, Aline Silva; Azevedo, Juliana
Abstract : Conservative clinical solutions, predictable esthetic, and immediate outcomes are important concepts of restorative dentistry. The aim of this case study was to recognize the selective enamel removal as an interesting conservative alternative to achieve optimal esthetic results and discuss the clinical protocol. This clinical report described an alternative esthetic and conservative treatment to transform the long and sharp aspect of the maxillary canines with a slightly aggressive aspect into features of slightly curved teeth with delicate lines. An accurate diagnostic and esthetic analysis of the smile was initially performed. The selective enamel removal was performed, and direct composite restoration was strategically placed. Clinical assessment showed good esthetic outcomes, enabling a smile harmony with an immediate, simple, and lower-cost technique. Practitioners should be exposed to conservative approaches to create esthetic smiles based on the selective enamel removal technique combined with composite resin.